The Changes of Immunohistochemistry in Lung Tissues, Surfactant Protein-D, eNOS, and NO in Mice Exposed to Essential Oil Vapor - Veterini, Anna Surgean; Putri, Herdiani Sulistyo; Dwiyatna, Archie Arman; Rahmah, Ainur; Satuman, Satuman; Rachmawati, Heni; Meirawan, Rizky Fajar; Sulistiawan, Soni Sunarso (Faculty of Medicine Universitas Airlangga, 2025)
Introduction: The use of essential oils in aromatherapy is widespread. However, few studies have explored the effects of smoke from the evaporation of commonly used essential oils. While essential oils are promoted for various benefits, prolonged exposure to inhaled particles from essential oil smoke may pose potential health risks. This study aimed to examine the effects of essential oil vapors on mice. Methods: This was an experimental study investigating the effects of different treatments on lung immunohistopathology, endothelial nitric oxide synthase (eNOS) expression, serum nitric oxide (NO) levels, and serum surfactant protein-D (SP-D) as an inflammation marker in mice. A total of 40 adult male Mus musculus mice (25–30 g) were randomly divided into four groups. Inflammation models were established by exposing the mice to a gas mixture containing vegetable glycerin, propylene glycol, and vitamin E acetate solution. Following inflammation induction, the mice received seven-day interventions with 0.9% NaCl solution, Eucalyptus globulus essential oil (EgEO), and citronella essential oil (CtEO), alongside an untreated inflammatory group. Results: The CtEO group intervention showed significant increases in eNOS expression (P=0.001) but no significant increase in NO compared to the other groups. The correlation analysis of eNOS expression in lung cells, serum NO, and SP-D levels was not significant, P>0.05 (p=0.160; p=0.115; p=0.234). Conclusion: Gas intervention containing 100% oxygen (O2) and CtEO steam increased eNOS expression on the immunohistochemistry (IHC) examination of mice.